KUAT TEKAN BETON SELF COMPACTING CONCRETE (SCC) TERHADAP PERBANDINGAN UKURAN AGREGAT KASAR - Edowinsyah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
This study discusses the comparison of the size of coarse aggregate to the compressive strength of SCC concrete which aims to determine the effect of good coarse aggregate size on the characteristics of SCC concrete. SCC is a fresh mix of concrete which is more fluid than normal concrete, the concrete can flow and compact itself to every corner of the building without the need for compaction equipment. The SCC concrete method in this study uses a superplasticizer which is added by chemicals and influences the size of the coarse aggregate. With the addition of 1.5% Superplaticizer to the weight of cement, the test on SCC concrete was seen on the compressive strength with the influence of aggregate size and Superplasticizer. The composition in making SCC concrete is cement, 3 (three) sizes of coarse aggregate, fine aggregate, water and superplasticizer, the highest compressive strength is the size of coarse aggregate 3cm aged 28 days due to the characteristics of coarse aggregate, the larger the split size, the harder the concrete texture. This solution causes the compressive strength of SCC concrete to be higher